Effects of cardiac contractility and vascular load on heart rate in athletes - Orel, V. R.; Tambovtseva, R. V. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to detect the peculiarities of the influence of cardiac contractility and vascular load on heart rate in athletes. Conclusion: - The correlation relationships between the heart rate and elastic resistance of the arterial system are positive and statistically significant both at rest and while performing muscular work on the cycle ergometer. - During muscular work on the cycle ergometer performed with the power of 500 and 1000 kg-m/min, the correlation relationships between the heart rate and peripheral resistance of the arterial system are positive, and HR increases statistically significantly with the increment of the peripheral resistance indices. - While performing muscular work on the cycle ergometer with the power of 500 and 1000 kg-m/min, the correlation relationships between the heart rate and average power of the left ventricular myocardium are positive, and HR increases statistically significantly with the increasing cardiac contractility.